STRENGTHENING THE ADMINISTRATIVE MANAGEMENT OF QUR’ANIC LEARNING CENTERS THROUGH A CONTINUOUS DEVELOPMENT PROGRAM IN SOUTH PURWOKERTO BANYUMAS - Sutrimo Purnomo; M. Hizbul Muflihin; Nurfuadi; M. Sholeh; Harisatunisa; Nurun Nafi’atul Hayati; Kunni Faizah Romadhoni; Shishi Mushokhiyah (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2026)
This community service program aims to strengthen the administrative management of Qur’anic Learning Centers in South Purwokerto through continuous mentoring. The program adopts a Community-Based Research (CBR) approach consisting of four main stages: laying the foundation, planning, information collection and analysis, and action based on the findings. The participants of this program were teachers of Qur’anic Learning Centers in South Purwokerto. Initial findings indicated that the administrative completeness of Qur’anic Learning Centers institutions was relatively low. Of the twenty-four types of administrative documents that should be available, only 55.50% of Qur’anic Learning Centers had met the required standards, while the remaining 44.50% did not yet possess adequate administrative documentation. To address this issue, a series of activities was conducted, including administrative management training, institutional mentoring, intensive coaching and field audits, as well as a Focus Group Discussion (FGD) to explore implications and evaluate the program. The program involved various stakeholders, including Badko LPQ (Coordinating Agency for Qur'anic Education Institutions) the Qur’anic Learning Centers of South Purwokerto Subdistrict and Banyumas Regency, the Takmir of Al-Birru Mosque, and academics from State Islamic University Saizu Purwokerto who served as resource persons and facilitators. The evaluation results show a significant improvement in the quality of Qur’anic Learning Center administrative management. Document completeness increased from 55.50% to 92.33%, while the proportion of institutions that had not yet met administrative standards decreased to 7.67%. The findings indicate that a systematic, collaborative, and sustained mentoring model is effective in enhancing the administrative management capacity of Qur’anic Learning Center teachers and administrators, enabling them to perform their duties in a more orderly, transparent, and accountable. The community service initiative provides strong evidence that strengthening administrative management through continuous assistance can significantly contribute to improving institutional capacity, managerial professionalism, and the overall quality of Qur’anic education services in South Purwokerto